High efficiency and energy saving aluminum alloy wire annealing furnace
By applying multi-efficient energy-saving and enhancing coatings on the inner wall of steel furnace linings and using plasma spraying technology to form multi-efficient energy-saving and enhancing coatings, the problems of insufficient bonding strength and poor thermal shock resistance of existing coatings are solved, and the effect of improving the thermal efficiency of the annealing furnace and extending the service life is achieved.
Patent Information
- Application Number
- CN202411675926.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The bonding strength of the existing annealing furnace coating is insufficient, the thermal shock resistance is poor, and it is easy to fall off, which affects the thermal efficiency and service life of the annealing furnace.
Multi-effect energy-saving reinforcement coating is used to form a multi-effect energy-saving reinforcement coating on the inner wall of the steel furnace lining through plasma spraying. The coating contains Cr2O3, Al2O3, SiO2, MnO2, Fe2O3 and metal-modified silicon carbide-graphene composite GO-NiCe@SiC as multi-effect reinforcement modification agent.
It significantly improves the infrared radiation performance and high temperature resistance of the furnace lining, improves the thermal efficiency of the annealing furnace, saves energy consumption, and enhances the thermal shock resistance of the coating, and extends the service life.
Smart Images

Figure CN119162444B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of annealing furnace equipment, and in particular to a high-efficiency and energy-saving aluminum alloy wire annealing furnace. Background Art
[0002] Aluminum alloy wires usually need to be annealed before use. This is because after a certain period of processing and stretching, the grains of the cable will gradually become larger and the grain boundaries will increase. This will cause the plasticity of the wire to deteriorate, and problems such as cracking and brittle cracking will occur when stretched or bent. Through annealing, the dislocations and grains in the wire can be rearranged, the size of the grains can be reduced, and the number of grain boundaries can be reduced, thereby improving the plasticity of the aluminum alloy wire.
[0003] Annealing furnace is the main equipment in the annealing process of aluminum alloy wire. The lining (usually made of heat-resistant steel) is usually set inside the annealing furnace. The lining can be replaced as a consumable material to facilitate the maintenance of the annealing furnace and extend its service life. It is usually necessary to protect the surface of the annealing furnace lining to reduce the direct erosion of the flame and high-temperature gas on the lining and increase the service life of the refractory in the furnace; at the same time, the infrared radiation performance (emissivity) of the lining is improved to improve the thermal efficiency of the annealing furnace and achieve the purpose of energy saving.
[0004] The use of high-emissivity infrared radiation coatings can improve the thermal efficiency of annealing furnaces and save energy. The main mechanisms are as follows: (1) Infrared radiation coatings can increase the emissivity of the furnace lining and enhance the radiation heat transfer of the inner wall after absorbing the heat from the heat source, while reducing the reflected part. This part of heat is easily absorbed by the combustion products (carbon dioxide, water vapor, etc.) and wasted with the furnace smoke; (2) Due to the absorption and radiation effect of the inner wall of the furnace lining, the wave spectrum of the thermal radiation in the furnace is changed, and the intermittent wave spectrum emitted by the heat source is converted into a continuous wave spectrum, which is beneficial to the absorption of the heated products and reduces the heat carried by the combustion products (Chen Wu. Preparation and research of high-temperature and high-emissivity infrared radiation coatings [D]. Wuhan University of Technology, 2008. DOI: 10.7666 / d.y1419581.).
[0005] The traditional coating preparation method is to use an inorganic binder to make a coating and then brush it on the inner wall of the furnace lining to form a coating. For example, the high-emissivity infrared energy-saving radiation coating and its preparation method disclosed in patent CN103589201B, the furnace body uniform temperature radiation coating and its preparation method disclosed in patent CN112048197A, etc. The coating prepared by this process has insufficient bonding strength with the substrate (furnace lining), poor thermal shock resistance, and is easy to fall off, affecting the thermal efficiency of the annealing furnace and shortening its service life. The plasma spraying process can improve the bonding strength of the interface between the coating and the substrate, such as the plasma spraying powder surface coating preparation method and surface coating and application disclosed in patent CN116875932B; therefore, plasma spraying can be used in the process of preparing coatings in furnace linings.
[0006] Silicon carbide material is a commonly used energy-saving coating with high strength, strong corrosion resistance, high emissivity and high temperature resistance, and a very low expansion coefficient (4.5*10 -6 / ℃), but it has the defects of poor dispersibility in metal-based coatings, low interfacial bonding strength with the metal substrate, and it is easily oxidized at high temperatures, resulting in reduced properties such as emissivity; these defects limit the application of silicon carbide in energy-saving coatings.
[0007] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a high-efficiency and energy-saving aluminum alloy wire annealing furnace in view of the deficiencies in the above-mentioned prior art.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: an efficient and energy-saving aluminum alloy wire annealing furnace, comprising an annealing furnace body, a steel lining arranged inside the annealing furnace body, a multi-effect energy-saving enhanced coating is arranged on the inner wall of the steel lining, and the multi-effect energy-saving enhanced coating is prepared by a plasma spraying process using a multi-effect energy-saving enhanced coating;
[0010] The raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0011] Cr2O3 7.0-16.5%, Al2O3 6.8-18.0%, SiO2 6-13.5%, MnO2 9-28%, multi-effect enhancing improver 12.5-35%, Fe2O3 10-37%; among them, the multi-effect enhancing improver is a metal-modified silicon carbide-graphene composite material: GO-NiCe@SiC.
[0012] Preferably, the multi-effect enhancing improver is prepared by the following method:
[0013] S1. preparing a composite complex of hydrazine hydrate, nickel and cerium: NiCe@HH;
[0014] S2, preparing an alkali-modified SiC dispersion;
[0015] S3. Preparation of precursor dispersion:
[0016] S3-1, preparing acidified graphene oxide;
[0017] S3-2, adding the acidified graphene oxide to deionized water, and ultrasonically dispersing the acidified graphene oxide dispersion, adding the obtained dispersion to the alkali-modified SiC dispersion prepared in step S2 under stirring, and ultrasonically dispersing n to obtain a precursor dispersion;
[0018] S4, preparation of multi-effect enhancing improver:
[0019] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the mixture is stirred under heating for reaction. After the reaction is completed, the mixture is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
[0020] Preferably, step S1 specifically comprises:
[0021] Add 0.025-0.1 mol of Ni(NO3)2·6H2O and 0.002-0.01 mol of Ce(NO3)3·6H2O to 100-400 mL of ethanol, stir at room temperature for 10-30 min, heat to 38-43°C, add 5-20 mL of N2H4·H2O dropwise in a nitrogen atmosphere, stir and react for 60-180 min in a nitrogen atmosphere after the addition is complete, vacuum filter after the reaction is completed, wash the solid product with ethanol, and vacuum dry at 20-30°C for 6-24 h to obtain NiCe@HH, which is sealed and stored.
[0022] Preferably, step S2 specifically comprises:
[0023] 0.25-1 mol of sodium hydroxide is added to 50-200 mL of deionized water, and stirred until completely dissolved. 1.75-7.0 g of SiC powder with a particle size of 2-20 μm is added under stirring, and ultrasonic dispersion is performed at 30-40° C. for 30-120 min to obtain an alkali-modified SiC dispersion.
[0024] Preferably, step S3 specifically comprises:
[0025] S3-1. Preparation of acidified graphene oxide:
[0026] 1.5-6 g of monolayer flaky graphene oxide powder is added to a mixed acid solution consisting of 10-40 mL of concentrated nitric acid with a mass fraction of 65-68% and 20-80 mL of concentrated sulfuric acid with a mass fraction of 93-98%, and treated for 0.5-2 h under stirring, filtered, and the solid product is washed with deionized water until neutral, and vacuum dried at 70-90° C. for 6-24 h to obtain acidified graphene oxide;
[0027] S3-2, taking 0.9-3.6 g of acidified graphene oxide and adding it to 25-100 mL of deionized water, ultrasonically dispersing it for 15-60 min, adding the obtained acidified graphene oxide dispersion to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically dispersing it for 15-60 min to obtain a precursor dispersion;
[0028] Preferably, step S4 is specifically:
[0029] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the mixture is stirred and reacted at 58-65° C. for 1-4 hours. After the reaction is completed, the mixture is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried at 50-65° C. for 12-36 hours to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
[0030] Preferably, the multi-effect enhancing improver is prepared by the following method:
[0031] S1. Preparation of the composite complex NiCe@HH of hydrazine hydrate, nickel and cerium:
[0032] 0.05 mol of Ni(NO3)2·6H2O and 0.005 mol of Ce(NO3)3·6H2O were added to 200 mL of ethanol, stirred at room temperature for 15 min, heated to 40°C, and 10 mL of N2H4·H2O was added dropwise in a nitrogen atmosphere. After the addition was completed, the mixture was stirred and reacted for 120 min in a nitrogen atmosphere. After the reaction was completed, vacuum filtration was performed, and the solid product was washed with ethanol and vacuum dried at 25°C for 12 h to obtain NiCe@HH, which was sealed and stored;
[0033] S2. Preparation of alkali-modified SiC dispersion:
[0034] 0.5 mol of sodium hydroxide was added to 100 mL of deionized water, and the mixture was stirred until completely dissolved. 3.5 g of SiC powder with a particle size of 5-15 μm was added under stirring, and ultrasonic dispersion was performed at 35° C. for 60 min to obtain an alkali-modified SiC dispersion.
[0035] S3. Preparation of precursor dispersion:
[0036] S3-1. Preparation of acidified graphene oxide:
[0037] 3 g of monolayer flaky graphene oxide powder was added into a mixed acid solution consisting of 20 mL of 65% by mass concentrated nitric acid and 40 mL of 95% by mass concentrated sulfuric acid, and treated for 1 h under stirring. The solid product was filtered and washed with deionized water until neutral, and vacuum dried at 80° C. for 12 h to obtain acidified graphene oxide.
[0038] S3-2, taking 1.8 g of acidified graphene oxide and adding it to 50 mL of deionized water, ultrasonically dispersing it for 30 min, adding the obtained acidified graphene oxide dispersion to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically dispersing it for 45 min to obtain a precursor dispersion;
[0039] S4, preparation of multi-effect enhancing improver:
[0040] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the reaction is stirred at 62° C. for 2 h. After the reaction is completed, it is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried at 60° C. for 24 h to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
[0041] Preferably, the preparation process of the multi-effect energy-saving enhanced coating comprises the following steps:
[0042] Step 1: Preparation of multi-effect energy-saving enhanced coating:
[0043] According to the weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect reinforcing agent and Fe2O3 powder are added into a ball mill, and the ball milling is performed for 2-8 hours, the ball milling speed is 100-450rpm, and the ball-to-material ratio is 7:1-12:1; the ball milling product is preheated at 130-200°C for 10-60min, and then sintered at 1100-1300°C for 1-3h, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving reinforcing coating;
[0044] Step 2: Pretreatment of the inner wall of the furnace lining:
[0045] The inner wall of the furnace lining is sandblasted, then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 120-180℃ with a plasma flame;
[0046] Step 3: Using the multi-effect energy-saving enhanced coating as raw material, a plasma spraying system is used to prepare the multi-effect energy-saving enhanced coating on the inner wall of the furnace lining.
[0047] Preferably, the preparation process of the multi-effect energy-saving enhanced coating comprises the following steps:
[0048] Step 1: Preparation of multi-effect energy-saving enhanced coating
[0049] According to the weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect reinforcing agent and Fe2O3 powder are added into a ball mill, and ball milled for 4 hours, with a ball milling speed of 180 rpm and a ball-to-material ratio of 10:1; the ball milled product is preheated at 150°C for 30 minutes, then sintered at 1200°C for 2 hours, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving reinforcing coating;
[0050] Step 2: Pretreatment of the inner wall of the furnace lining:
[0051] The inner wall of the furnace lining is sandblasted, then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 150°C with a plasma flame;
[0052] Step 3: Using the multi-effect energy-saving enhanced coating as a raw material, a plasma spraying system is used to prepare a multi-effect energy-saving enhanced coating on the inner wall of the furnace lining;
[0053] Among them, the process parameters of the plasma spraying system are: a mixture of argon and nitrogen as the feeding protective gas, and an argon flow rate of 1.1-1.5m 3 / h, nitrogen flow rate 0.4-0.95m 3 / h, plasma arc voltage 60-80V, current 400-600A, feeding speed 13-38g / min, spraying distance 50-95mm; the thickness of the multi-effect energy-saving enhanced coating is 0.1-0.5mm.
[0054] Preferably, the process parameters of the plasma spraying system are: a mixture of argon and nitrogen as the feeding protective gas, an argon flow rate of 1.3m 3 / h, nitrogen flow rate 0.75m 3 / h, plasma arc voltage 75V, current 500A, feeding speed 25g / min, spraying distance 80mm; the thickness of the multi-effect energy-saving enhanced coating is 0.2mm.
[0055] The beneficial effects of the present invention are:
[0056] The present invention provides a high-efficiency and energy-saving aluminum alloy wire annealing furnace. By arranging a multi-effect energy-saving enhanced coating on the inner wall of a steel furnace lining, the infrared radiation performance and high temperature resistance of the furnace lining can be significantly improved, the efficiency of the annealing furnace can be improved, and energy consumption can be saved. In the present invention, a plasma spraying process is used to form the multi-effect energy-saving enhanced coating, which can improve the bonding strength between the coating and the substrate (steel furnace lining);
[0057] In the multi-effect energy-saving enhanced coating of the present invention, the infrared radiation performance of the coating can be significantly improved by adding a multi-effect enhancement modifier, and the emissivity can be increased, thereby improving thermal efficiency and saving energy consumption; at the same time, the thermal expansion coefficient of the prepared coating can be reduced, and the bonding strength between the coating and the substrate can be enhanced, thereby improving the thermal shock resistance of the coating and extending the service life;
[0058] The multi-effect enhancing improver provided by the present invention is a composite structure system in which SiC particles coated with Ni and Ce nanoparticle layers on the surface are grafted on flaky graphene oxide in large quantities. In the composite structure system: (1) the co-coating of Ni and Ce nanoparticles can greatly improve the compatibility between SiC particles and other metal oxide components in the coating. Ni can form NiFe alloy with iron in the substrate (steel furnace lining), which can improve the bonding strength between the coating and the substrate; the coating effect of Ni and Ce nanoparticles can solve the problem of poor dispersibility of SiC particles in metal-based coatings, and can also effectively overcome the defect that SiC particles are easily oxidized at high temperatures; (2) with the help of the bridging effect of the composite complex ions, a large number of metal Ce and Ni-coated SiC particles can be grafted on the graphene oxide. Ce and Ni can improve its compatibility with the metal-based coating system and reduce its agglomeration. The grafted particles The pulling effect on the flake graphene oxide can cause it to unfold into a plane and reduce its curling; the dual effect can achieve uniform dispersion of the flake graphene oxide in the coating system and help it unfold in the system in a plane form. With the help of the strong thermal conductivity and high emissivity of graphene oxide, a large number of thermal conductive network structures can be constructed in the coating, which can ultimately significantly improve the infrared radiation performance, reduce thermal expansion, improve thermal stability, and improve the thermal shock resistance of the coating; (3) Rare earth Ce can form coordination bonds with the oxygen-containing functional groups on graphene oxide. The introduction of new functional groups can reduce the surface energy and interface energy of graphene oxide, thereby improving the dispersibility of graphene oxide; on the other hand, rare earth Ce can also refine the grains, improve the corrosion resistance of the coating, and enhance the bonding strength of the coating; the introduction of Ce in the form of Ce and Ni co-doping can facilitate the uniform dispersion of Ce in the coating system. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 is the XRD pattern of the multi-effect enhancing modifier prepared in Example 1;
[0060] Figure 2 The coating emissivity test results in the test case are shown in FIG.
[0061] Figure 3 2 is the temperature rise comparison result of the annealing furnace in the test example. DETAILED DESCRIPTION
[0062] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0063] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0064] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0065] The present invention provides a high-efficiency energy-saving aluminum alloy wire annealing furnace, comprising an annealing furnace body, a steel lining arranged inside the annealing furnace body, a multi-effect energy-saving enhanced coating arranged on the inner wall of the steel lining, and the multi-effect energy-saving enhanced coating is prepared by a plasma spraying process using a multi-effect energy-saving enhanced coating;
[0066] The raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0067] Cr2O3 7.0-16.5%, Al2O3 6.8-18.0%, SiO2 6-13.5%, MnO2 9-28%, multi-effect enhancing improver 12.5-35%, Fe2O3 10-37%; among them, the multi-effect enhancing improver is a metal-modified silicon carbide-graphene composite material: GO-NiCe@SiC.
[0068] The steel furnace lining is made of conventional heat-resistant steel, such as Cr25Ni20.
[0069] In a preferred embodiment, the preparation process of the multi-effect energy-saving enhanced coating comprises the following steps:
[0070] Step 1: Preparation of multi-effect energy-saving enhanced coating:
[0071] According to the weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect reinforcing agent and Fe2O3 powder are added into a ball mill, and the ball milling is performed for 2-8 hours, the ball milling speed is 100-450rpm, and the ball-to-material ratio is 7:1-12:1; the ball milling product is preheated at 130-200°C for 10-60min, and then sintered at 1100-1300°C for 1-3h, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving reinforcing coating;
[0072] Step 2: Pretreatment of the inner wall of the furnace lining:
[0073] The inner wall of the furnace lining is sandblasted, then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 120-180℃ with a plasma flame;
[0074] Step 3: Using the multi-effect energy-saving enhanced coating as raw material, a plasma spraying system is used to prepare the multi-effect energy-saving enhanced coating on the inner wall of the furnace lining.
[0075] In a preferred embodiment, the process parameters of the plasma spraying system are: a mixture of argon and nitrogen is used as the feeding protective gas, and the argon flow rate is 1.1-1.5m 3 / h, nitrogen flow rate 0.4-0.95m 3 / h, plasma arc voltage 60-80V, current 400-600A, feeding speed 13-38g / min, spraying distance 50-95mm; the thickness of the multi-effect energy-saving enhanced coating is controlled to be 0.1-0.5mm.
[0076] In a preferred embodiment, the multi-effect enhancing improver is prepared by the following method:
[0077] S1. Preparation of a composite complex of hydrazine hydrate, nickel and cerium: NiCe@HH:
[0078] Add 0.025-0.1 mol of Ni(NO3)2·6H2O and 0.002-0.01 mol of Ce(NO3)3·6H2O to 100-400 mL of ethanol, stir at room temperature for 10-30 min, heat to 38-43°C, add 5-20 mL of N2H4·H2O dropwise in a nitrogen atmosphere, stir and react for 60-180 min in a nitrogen atmosphere after the addition is complete, vacuum filter after the reaction is complete, wash the solid product with ethanol, vacuum dry at 20-30°C for 6-24 h to obtain NiCe@HH, and seal and store;
[0079] S2. Preparation of alkali-modified SiC dispersion:
[0080] Add 0.25-1 mol of sodium hydroxide to 50-200 mL of deionized water, stir until completely dissolved, add 1.75-7.0 g of SiC powder with a particle size of 2-20 μm under stirring, and ultrasonically disperse at 30-40° C. for 30-120 min to obtain an alkali-modified SiC dispersion;
[0081] S3. Preparation of precursor dispersion:
[0082] S3-1. Preparation of acidified graphene oxide:
[0083] 1.5-6 g of monolayer flaky graphene oxide powder is added to a mixed acid solution consisting of 10-40 mL of concentrated nitric acid with a mass fraction of 65-68% and 20-80 mL of concentrated sulfuric acid with a mass fraction of 93-98%, and treated for 0.5-2 h under stirring, filtered, and the solid product is washed with deionized water until neutral, and vacuum dried at 70-90° C. for 6-24 h to obtain acidified graphene oxide;
[0084] S3-2, taking 0.9-3.6 g of acidified graphene oxide and adding it to 25-100 mL of deionized water, ultrasonically dispersing it for 15-60 min, adding the obtained acidified graphene oxide dispersion to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically dispersing it for 15-60 min to obtain a precursor dispersion;
[0085] S4, preparation of multi-effect enhancing improver:
[0086] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the reaction is stirred at 58-65° C. for 1-4 hours. After the reaction is completed, it is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol, and vacuum dried at 50-65° C. for 12-36 hours to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., a multi-effect enhancing modifier.
[0087] The present invention can significantly improve the infrared radiation performance and high temperature resistance of the furnace lining by arranging a multi-effect energy-saving enhanced coating on the inner wall of the steel furnace lining, improve the efficiency of the annealing furnace, and save energy consumption. Among them, the multi-effect energy-saving enhanced coating is formed by a plasma spraying process, which can improve the bonding strength between the coating and the substrate (steel furnace lining).
[0088] In the multi-effect energy-saving enhanced coating of the present invention, by adding a multi-effect enhancing modifier, the infrared radiation performance of the coating can be significantly improved, the emissivity can be increased, thereby improving thermal efficiency and saving energy consumption; at the same time, the thermal expansion coefficient of the prepared coating can be reduced, and the bonding strength between the coating and the substrate can be enhanced, thereby improving the thermal shock resistance of the coating and extending the service life. The main mechanism is explained below.
[0089] (1) In the present invention, Ni 2+ 、Ce 3+ It forms a composite complex NiCe@HH with hydrazine hydrate;
[0090] SiC is modified by a strong alkaline solution. The alkaline solution makes the pH value of the system far away from the isoelectric point of SiC (pH=3-4), so that a large number of hydroxyl groups are adsorbed on the surface of SiC. The surface of the monolayer flake graphene oxide powder after acidification is rich in oxygen-containing functional groups such as carboxyl and hydroxyl groups.
[0091] After NiCe@HH is mixed with modified SiC and acidified graphene oxide, the positively charged complex ions can coordinate with the hydroxyl groups on the SiC surface, react to generate metal hydroxide precipitates and deposit evenly on the surface of SiC particles. On the other hand, the complex ions can also coordinate with or react with the carboxyl and hydroxyl groups on the surface of acidified graphene oxide, so that a large number of SiC particles are grafted onto the acidified graphene oxide. Finally, the complex ions can play a bridging role, so that a large number of SiC particles with hydroxide precipitates deposited on the surface are grafted onto the acidified graphene oxide. Afterwards, a large number of hydroxide precipitates are reduced to Ni and Ce metal nanoparticles under the strong reducing effect of hydrazine hydrate, and finally a composite structure system is constructed in which SiC particles with Ni and Ce nanoparticle layers on the surface are grafted on flaky graphene oxide in large quantities, namely GO-NiCe@SiC.
[0092] (2) SiC has high strength, strong corrosion resistance, high emissivity and high temperature resistance, and a very low expansion coefficient (about 4.5*10 -6 / ℃), but it has the defects of poor dispersibility in metal-based coatings and low interfacial bonding strength with the metal substrate, and it is easily oxidized at high temperatures, resulting in reduced properties such as emissivity.
[0093] In the composite structure system of the present invention, the co-coating of Ni and Ce nanoparticles can greatly improve the compatibility between SiC particles and other metal oxide components in the coating. Ni can form NiFe alloy with iron in the substrate (steel furnace lining), which can improve the bonding strength between the coating and the substrate. The coating effect of Ni and Ce nanoparticles can solve the problem of poor dispersibility of SiC particles in metal-based coatings, and can also effectively overcome the defect that SiC particles are easily oxidized at high temperatures.
[0094] (2) Graphene oxide theoretically has extremely high thermal conductivity and emissivity, and low thermal expansion, but it is easy to agglomerate and curl, which will greatly reduce its thermal conductivity and emissivity. In the present invention, with the help of the bridging effect of the composite complex ions, a large number of metal Ce and Ni-coated SiC particles can be grafted onto graphene oxide. Ce and Ni can improve its compatibility with the metal-based coating system and reduce its agglomeration. The pulling effect of the grafted particles on the flake graphene oxide can promote its unfolding to form a plane and reduce its curling; under the dual effect, the flake graphene oxide can be evenly dispersed in the coating system and help it unfold in the system in a plane form. With the help of the strong thermal conductivity and high emissivity of graphene oxide, a large number of thermal conductive network structures can be constructed in the coating, which can ultimately significantly improve the infrared radiation performance, reduce thermal expansion, improve thermal stability, and improve the thermal shock resistance of the coating.
[0095] (3) Rare earth Ce can form coordination bonds with oxygen-containing functional groups on graphene oxide. The introduction of new functional groups can reduce the surface energy and interface energy of graphene oxide, thereby improving the dispersibility of graphene oxide. On the other hand, rare earth Ce can also refine the grains, improve the corrosion resistance of the coating, and enhance the bonding strength of the coating. The introduction of Ce in the form of co-doping with Ni can facilitate the uniform dispersion of Ce in the coating system.
[0096] During the sintering process, rare earth Ce forms CeO2, which has a multi-layer electronic structure. Doping into the main lattice system can introduce impurity energy levels and oxygen vacancies, increasing the number of electrons and holes (Ce 4+ The ionic radius of Ni 2+ Cr 3+ Close to, can be dissolved into the main lattice system, Ce 4+ Replace Ni 2+ Cr 3+ When plasma is generated, holes will be generated in the unit cell, which will cause lattice distortion and destroy the original lattice vibration, increase the lattice vibration frequency, and improve the infrared radiation performance of the system), promote carrier absorption, and at the same time, the radius difference with other elements and the introduction of oxygen vacancies can form more lattice distortion, thereby enhancing the absorption of infrared radiation by lattice vibration (Zhang Baoku. Research on the process preparation and performance of rare earth oxide composite mixed spinel [D]. Wuhan University of Technology [2024-04-17].), which can ultimately improve the emissivity of the system.
[0097] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0098] Description of main raw materials and instruments:
[0099] Among the raw materials for preparing the multi-effect energy-saving enhanced coating involved below, Cr2O3 15%, Al2O3 13%, SiO2 10%, MnO2, and Fe2O3 are all conventional commercially available products, and the particle size is less than 200 meshes;
[0100] Single-layer graphene oxide powder (GO), flake diameter: 0.5-5 μm, thickness: 0.8-1.2 nm; purchased from Nanjing Xianfeng Nanomaterials Technology Co., Ltd.
[0101] SiC, average particle size 10 μm, purchased from Shanghai Fuzhe Chemical Co., Ltd.;
[0102] The furnace lining is made of heat-resistant steel Cr25Ni20;
[0103] Plasma spraying system, SX-80 plasma spraying system, Guangzhou Sanxin Metal Technology Co., Ltd.;
[0104] The other reagents used are all common products that can be purchased commercially.
[0105] Example 1
[0106] A high-efficiency and energy-saving aluminum alloy wire annealing furnace comprises an annealing furnace body and a steel lining arranged inside the annealing furnace body, wherein a multi-effect energy-saving enhanced coating is arranged on the inner wall of the steel lining, wherein the preparation process of the multi-effect energy-saving enhanced coating comprises the following steps:
[0107] Step 1: Preparation of multi-effect energy-saving enhanced coating:
[0108] The raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0109] Cr2O3 15%, Al2O3 13%, SiO2 10%, MnO2 17%, multi-effect enhancing agent 25% and the balance Fe2O3; wherein the multi-effect enhancing agent is a metal-modified silicon carbide-graphene composite material: GO-NiCe@SiC;
[0110] According to the above weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect enhancing modifier and Fe2O3 powder are added into a ball mill, and ball milled for 4 hours, with a ball milling speed of 180 rpm and a ball-to-material ratio of 10:1; the ball milled product is preheated at 150°C for 30 minutes, then sintered at 1200°C for 2 hours, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving enhancing coating;
[0111] Step 2: Pretreatment of the inner wall of the furnace lining:
[0112] The inner wall of the furnace lining was sandblasted (120 mesh corundum blasting, blasting pressure 350kpa, blasting time 5min), then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 150℃ with a plasma flame;
[0113] Step 3: Using the multi-effect energy-saving enhanced coating as raw material, a plasma spraying system is used to prepare a multi-effect energy-saving enhanced coating on the inner wall of the furnace lining; the process parameters of the plasma spraying system are: a mixed gas of argon and nitrogen as the feeding protective gas, and an argon flow rate of 1.3m 3 / h, nitrogen flow rate 0.75m 3 / h, plasma arc voltage 75V, current 500A, feeding speed 25g / min, spraying distance 80mm; the thickness of the multi-effect energy-saving enhanced coating is 0.2mm.
[0114] In this embodiment, the multi-effect enhancing improver is prepared by the following method:
[0115] S1. Preparation of the composite complex NiCe@HH of hydrazine hydrate, nickel and cerium:
[0116] 0.05 mol of Ni(NO3)2·6H2O and 0.005 mol of Ce(NO3)3·6H2O were added to 200 mL of ethanol, stirred at room temperature for 15 min, heated to 40°C, and 10 mL of N2H4·H2O was added dropwise in a nitrogen atmosphere. After the addition was completed, the mixture was stirred and reacted for 120 min in a nitrogen atmosphere. After the reaction was completed, vacuum filtration was performed, and the solid product was washed with ethanol and vacuum dried at 25°C for 12 h to obtain NiCe@HH, which was sealed and stored;
[0117] S2. Preparation of alkali-modified SiC dispersion:
[0118] 0.5 mol of sodium hydroxide was added to 100 mL of deionized water, and the mixture was stirred until completely dissolved. 3.5 g of SiC powder with a particle size of 5-15 μm was added under stirring, and ultrasonic dispersion was performed at 35° C. for 60 min to obtain an alkali-modified SiC dispersion.
[0119] S3. Preparation of precursor dispersion:
[0120] S3-1. Preparation of acidified graphene oxide:
[0121] 3 g of monolayer flaky graphene oxide powder was added into a mixed acid solution consisting of 20 mL of 65% by mass concentrated nitric acid and 40 mL of 95% by mass concentrated sulfuric acid, and treated for 1 h under stirring. The solid product was filtered and washed with deionized water until neutral, and vacuum dried at 80° C. for 12 h to obtain acidified graphene oxide.
[0122] S3-2, taking 1.8 g of acidified graphene oxide and adding it to 50 mL of deionized water, ultrasonically dispersing it for 30 min, adding the obtained acidified graphene oxide dispersion to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically dispersing it for 45 min to obtain a precursor dispersion;
[0123] S4, preparation of multi-effect enhancing improver:
[0124] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 was added to the precursor dispersion prepared in step S3, and the reaction was stirred at 62°C for 2h. After the reaction was completed, it was cooled to room temperature and vacuum filtered. The solid product was washed with ethanol and vacuum dried at 60°C for 24h to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., a multi-effect enhancing modifier.
[0125] Example 2
[0126] This example is basically the same as Example 1, except that: in this example, the raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0127] Cr2O3 15%, Al2O3 13%, SiO2 10%, MnO2 17%, multi-effect enhancing improver 23% and the balance Fe2O3.
[0128] Example 3
[0129] This example is basically the same as Example 1, except that: in this example, the raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0130] Cr2O3 16.5%, Al2O3 12%, SiO2 9.5%, MnO2 18%, multi-effect enhancing improver 25% and the balance Fe2O3.
[0131] Comparative Example 1
[0132] This example is basically the same as Example 1, except that: in this example, the raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0133] Cr2O3 18%, Al2O3 16%, SiO2 14%, MnO2 22% and the balance Fe2O3.
[0134] Comparative Example 2
[0135] This example is basically the same as Example 1, except that: in this example, the raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage:
[0136] Cr2O3 15%, Al2O3 13%, SiO2 10%, MnO2 17%, Ni 8.3%, Ce 2%, SiC 9.8%, GO 5% and the balance Fe2O3. Among them, Ni and Ce are powders below 200 mesh, and the sources of SiC and GO (single-layer flake graphene oxide powder) are the same as those in Example 1.
[0137] Comparative Example 3
[0138] This example is basically the same as Example 1, except that in this example, the multi-effect enhancing improver is prepared by the following method:
[0139] S1. Preparation of the composite complex Ni@HH of hydrazine hydrate and nickel:
[0140] 0.05 mol of Ni(NO3)2·6H2O was added to 200 mL of ethanol, stirred at room temperature for 15 min, heated to 40°C, and 10 mL of N2H4·H2O was added dropwise in a nitrogen atmosphere. After the addition was completed, the mixture was stirred and reacted for 120 min in a nitrogen atmosphere. After the reaction was completed, vacuum filtration was performed, and the solid product was washed with ethanol and vacuum dried at 25°C for 12 h to obtain Ni@HH, which was sealed and stored;
[0141] Ni@HH was used to replace NiCe@HH in Example 1, and the remaining steps were the same as those in Example 1.
[0142] Comparative Example 4
[0143] This example is basically the same as Example 1, except that in this example, the multi-effect enhancing improver is prepared by the following method:
[0144] S1, preparing a composite complex of hydrazine hydrate, nickel and cerium NiCe@HH, the same as in Example 1;
[0145] S2, preparing an alkali-modified SiC dispersion, the same as in Example 1;
[0146] S3, preparation of multi-effect enhancing improver:
[0147] In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 was added to the alkali-modified SiC dispersion prepared in step S2, and the mixture was stirred and reacted at 62°C for 2 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum filtered. The solid product was washed with ethanol and vacuum dried at 60°C for 24 h to obtain a multi-effect enhancing improver.
[0148] Comparative Example 5
[0149] This example is basically the same as Example 1, except that in this example, the multi-effect enhancing improver is prepared by the following method:
[0150] S1. Preparation of the composite complex Ni@HH of hydrazine hydrate and nickel:
[0151] 0.05 mol of Ni(NO3)2·6H2O was added to 200 mL of ethanol, stirred at room temperature for 15 min, heated to 40°C, and 10 mL of N2H4·H2O was added dropwise in a nitrogen atmosphere. After the addition was completed, the mixture was stirred and reacted for 120 min in a nitrogen atmosphere. After the reaction was completed, vacuum filtration was performed, and the solid product was washed with ethanol and vacuum dried at 25°C for 12 h to obtain Ni@HH, which was sealed and stored;
[0152] S2, preparing an alkali-modified SiC dispersion, the same as in Example 1;
[0153] S3, preparation of multi-effect enhancing improver:
[0154] In a nitrogen atmosphere, under continuous stirring, all the NiC@HH prepared in step S1 was added to the alkali-modified SiC dispersion prepared in step S2, and the mixture was stirred and reacted at 62°C for 2 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum filtered. The solid product was washed with ethanol and vacuum dried at 60°C for 24 h to obtain a multi-effect enhancing improver.
[0155] Test Case
[0156] 1. Reference Figure 1 , is the XRD diagram of the multi-effect enhancing modifier prepared in Example 1.
[0157] Second, a Cr25Ni20 heat-resistant steel substrate (the same material as the furnace lining) was used to prepare several substrate samples with a size of 50 mm × 25 mm × 10 mm. The multi-effect energy-saving enhanced coating was prepared on the substrate sample using the same method as the above embodiments and comparative examples (i.e., the substrate sample was used instead of the furnace lining). The obtained test samples (respectively recorded as embodiments 1-3 and comparative examples 1-5) were subjected to the following performance tests:
[0158] (1) Emissivity:
[0159] With reference to the standard "GJB 5023.2-2003 Emissivity and emissivity test methods for materials and coatings Part 2: Emissivity", the measurement was carried out using an IRE-2 infrared radiation tester (Beijing Zhongke Optical Analysis Chemical Technology Research Institute), with a measurement temperature of 500~900℃ and a spectral range of 2~14μm.
[0160] The average emissivity in the above spectral range was measured at different temperatures. The measurement results are shown in Table 1 and Figure 2 As shown:
[0161] Table 1
[0162]
[0163] It can be seen from the test results that the emissivity of Examples 1-3 is relatively high, while Comparative Examples 1-5 show varying degrees of decline; Comparative Example 1 has the largest decline, which is attributed to the fact that no multi-effect enhancing modifier is added to the coating; although Comparative Example 2 also adds Ni, Ce, SiC, and GO with the same composition as the multi-effect enhancing modifier in Example 1, they are directly added to the raw materials without constructing a GO-NiCe@SiC composite structure system as in Example 1, and cannot effectively solve the natural defects of SiC, GO, etc., resulting in a low emissivity; and the results of Comparative Examples 3-5 show that in the composite structure system GO-NiCe@SiC, GO and Ce can play multiple enhancing roles, and the structural system constructed by the cooperation of the two can significantly improve the emissivity of the final coating.
[0164] (2) Coating bonding strength
[0165] The test was carried out using a tensile testing machine in accordance with the standard GB / T 8642-2002 Determination of tensile bonding strength of thermal spraying. The test results are shown in Table 2 below:
[0166] Table 2
[0167] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Bonding strength / MPa 33.7 33.1 33.5 20.4 23.9 29.4 26.7 28.2
[0168] It can be seen from the test results that the bonding strength between the coating and the substrate of Examples 1-3 is high, while that of Comparative Examples 1-5 decreases to varying degrees.
[0169] (3) Thermal stability test
[0170] Thermal shock resistance test: Heat the sample to 800℃, keep it warm for 15 minutes, and then air cool it to room temperature. This is a thermal cycle. Cycle 500 times and observe whether there are cracks on the coating surface.
[0171] After 500 thermal shock cycles, the emissivity (average value in the temperature range of 500-900°C, spectral range of 2-14 μm) and coating bonding strength of the sample were tested according to the method (1) above;
[0172] The test results are shown in Table 3 below:
[0173] Table 3
[0174]
[0175] It can be seen from the test results that the coatings of Examples 1-3 have excellent thermal shock resistance, which is significantly better than that of Comparative Examples 1-5.
[0176] The annealing furnace of Example 1 and the annealing furnace without the multi-effect energy-saving enhanced coating (the rest of the results are exactly the same as the annealing furnace of Example 1, as a control example) were used for temperature comparison. The test results are as follows: Figure 3 As shown, it can be seen from the test results that, compared with the control example, the coating of Example 1 has strong thermal radiation performance, which can effectively improve the thermal efficiency of the annealing furnace and save energy consumption.
[0177] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. An efficient and energy-saving aluminum alloy wire annealing furnace, comprising an annealing furnace body and a steel lining arranged inside the annealing furnace body, characterized in that: The inner wall of the steel furnace lining is provided with a multi-effect energy-saving enhanced coating, and the multi-effect energy-saving enhanced coating is prepared by a plasma spraying process using a multi-effect energy-saving enhanced coating; The raw materials for preparing the multi-effect energy-saving enhanced coating include, by weight percentage: Cr2O3 7.0-16.5%, Al2O3 6.8-18.0%, SiO2 6-13.5%, MnO2 9-28%, multi-effect enhancing improver 12.5-35%, Fe2O3 10-37%; among them, the multi-effect enhancing improver is a metal-modified silicon carbide-graphene composite material: GO-NiCe@SiC.
2. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 1, characterized in that: The multi-effect enhancing improver is prepared by the following method: S1. preparing a composite complex of hydrazine hydrate, nickel and cerium: NiCe@HH; S2, preparing an alkali-modified SiC dispersion; S3. Preparation of precursor dispersion: S3-1, preparing acidified graphene oxide; S3-2, adding the acidified graphene oxide to deionized water, and ultrasonically dispersing the acidified graphene oxide dispersion, adding the obtained dispersion to the alkali-modified SiC dispersion prepared in step S2 under stirring, and ultrasonically dispersing n to obtain a precursor dispersion; S4, preparation of multi-effect enhancing improver: In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the mixture is stirred under heating for reaction. After the reaction is completed, the mixture is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
3. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 2, characterized in that: Step S1 is specifically as follows: Add 0.025-0.1 mol of Ni(NO3)2·6H2O and 0.002-0.01 mol of Ce(NO3)3·6H2O to 100-400 mL of ethanol, stir at room temperature for 10-30 min, heat to 38-43°C, add 5-20 mL of N2H4·H2O dropwise in a nitrogen atmosphere, stir and react for 60-180 min in a nitrogen atmosphere after the addition is complete, vacuum filter after the reaction is completed, wash the solid product with ethanol, and vacuum dry at 20-30°C for 6-24 h to obtain NiCe@HH, which is sealed and stored.
4. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 2, characterized in that: Step S2 is specifically as follows: 0.25-1 mol of sodium hydroxide is added to 50-200 mL of deionized water, and stirred until completely dissolved. 1.75-7.0 g of SiC powder with a particle size of 2-20 μm is added under stirring, and ultrasonic dispersion is performed at 30-40° C. for 30-120 min to obtain an alkali-modified SiC dispersion.
5. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 2, characterized in that: Step S3 is specifically as follows: S3-1. Preparation of acidified graphene oxide: 1.5-6 g of monolayer flaky graphene oxide powder is added to a mixed acid solution consisting of 10-40 mL of concentrated nitric acid with a mass fraction of 65-68% and 20-80 mL of concentrated sulfuric acid with a mass fraction of 93-98%, and treated for 0.5-2 h under stirring, filtered, and the solid product is washed with deionized water until neutral, and vacuum dried at 70-90° C. for 6-24 h to obtain acidified graphene oxide; S3-2, take 0.9-3.6g of acidified graphene oxide and add it to 25-100mL of deionized water, and ultrasonically disperse it for 15-60min. The obtained acidified graphene oxide dispersion is added to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically disperse it for 15-60min to obtain a precursor dispersion.
6. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 2, characterized in that: Step S4 is specifically as follows: In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the mixture is stirred and reacted at 58-65° C. for 1-4 hours. After the reaction is completed, the mixture is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried at 50-65° C. for 12-36 hours to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
7. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 2, characterized in that: The multi-effect enhancing improver is prepared by the following method: S1. Preparation of the composite complex NiCe@HH of hydrazine hydrate, nickel and cerium: 0.05 mol of Ni(NO3)2·6H2O and 0.005 mol of Ce(NO3)3·6H2O were added to 200 mL of ethanol, stirred at room temperature for 15 min, heated to 40°C, and 10 mL of N2H4·H2O was added dropwise in a nitrogen atmosphere. After the addition was completed, the mixture was stirred and reacted for 120 min in a nitrogen atmosphere. After the reaction was completed, vacuum filtration was performed, and the solid product was washed with ethanol and vacuum dried at 25°C for 12 h to obtain NiCe@HH, which was sealed and stored; S2. Preparation of alkali-modified SiC dispersion: 0.5 mol of sodium hydroxide was added to 100 mL of deionized water, and the mixture was stirred until completely dissolved. 3.5 g of SiC powder with a particle size of 5-15 μm was added under stirring, and ultrasonic dispersion was performed at 35° C. for 60 min to obtain an alkali-modified SiC dispersion. S3. Preparation of precursor dispersion: S3-1. Preparation of acidified graphene oxide: 3 g of monolayer flaky graphene oxide powder was added into a mixed acid solution consisting of 20 mL of 65% by mass concentrated nitric acid and 40 mL of 95% by mass concentrated sulfuric acid, and treated for 1 h under stirring. The solid product was filtered and washed with deionized water until neutral, and vacuum dried at 80° C. for 12 h to obtain acidified graphene oxide. S3-2, taking 1.8 g of acidified graphene oxide and adding it to 50 mL of deionized water, ultrasonically dispersing it for 30 min, adding the obtained acidified graphene oxide dispersion to the alkali-modified SiC dispersion obtained in step S2 under stirring, and ultrasonically dispersing it for 45 min to obtain a precursor dispersion; S4, preparation of multi-effect enhancing improver: In a nitrogen atmosphere, under continuous stirring, all the NiCe@HH prepared in step S1 is added to the precursor dispersion prepared in step S3, and the reaction is stirred at 62° C. for 2 h. After the reaction is completed, it is cooled to room temperature, vacuum filtered, and the solid product is washed with ethanol and vacuum dried at 60° C. for 24 h to obtain a metal-modified silicon carbide-graphene composite material GO-NiCe@SiC, i.e., the multi-effect enhancing improver.
8. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 1, characterized in that: The preparation process of the multi-effect energy-saving enhanced coating includes the following steps: Step 1: Preparation of multi-effect energy-saving enhanced coating: According to the weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect reinforcing agent and Fe2O3 powder are added into a ball mill, and the ball milling is performed for 2-8 hours, the ball milling speed is 100-450rpm, and the ball-to-material ratio is 7:1-12:1; the ball milling product is preheated at 130-200°C for 10-60min, and then sintered at 1100-1300°C for 1-3h, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving reinforcing coating; Step 2: Pretreatment of the inner wall of the furnace lining: The inner wall of the furnace lining is sandblasted, then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 120-180℃ with a plasma flame; Step 3: Using the multi-effect energy-saving enhanced coating as raw material, a plasma spraying system is used to prepare the multi-effect energy-saving enhanced coating on the inner wall of the furnace lining.
9. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 8, characterized in that: The preparation process of the multi-effect energy-saving enhanced coating includes the following steps: Step 1: Preparation of multi-effect energy-saving enhanced coating According to the weight ratio, Cr2O3 powder, Al2O3 powder, SiO2 powder, MnO2 powder, multi-effect reinforcing agent and Fe2O3 powder are added into a ball mill, and ball milled for 4 hours, with a ball milling speed of 180 rpm and a ball-to-material ratio of 10:1; the ball milled product is preheated at 150°C for 30 minutes, then sintered at 1200°C for 2 hours, cooled to room temperature with the furnace, and ground into powder to obtain a multi-effect energy-saving reinforcing coating; Step 2: Pretreatment of the inner wall of the furnace lining: The inner wall of the furnace lining is sandblasted, then cleaned with acetone and ethanol in turn, dried with hot air, and then preheated to 150°C with a plasma flame; Step 3: Using the multi-effect energy-saving enhanced coating as a raw material, a plasma spraying system is used to prepare a multi-effect energy-saving enhanced coating on the inner wall of the furnace lining; Among them, the process parameters of the plasma spraying system are: a mixture of argon and nitrogen as the feeding protective gas, and an argon flow rate of 1.1-1.5m 3 / h, nitrogen flow rate 0.4-0.95m 3 / h, plasma arc voltage 60-80V, current 400-600A, feeding speed 13-38g / min, spraying distance 50-95mm; the thickness of the multi-effect energy-saving enhanced coating is 0.1-0.5mm.
10. The high-efficiency and energy-saving aluminum alloy wire annealing furnace according to claim 9, characterized in that: in, The process parameters of the plasma spraying system are: a mixture of argon and nitrogen as the feeding protective gas, and an argon flow rate of 1.3m 3 / h, nitrogen flow rate 0.75m 3 / h, plasma arc voltage 75V, current 500A, feeding speed 25g / min, spraying distance 80mm; The thickness of the multi-effect energy-saving enhanced coating is 0.2mm.
Citation Information
Patent Citations
High emissivity infrared energy-saving radiation coating and its preparation method
CN103589201B
Furnace body uniform-temperature radiation coating and preparation method thereof
CN112048197A
Energy-saving high-temperature radiating spray coating material for silicon steel annealing furnace as well as preparation method and application thereof
CN109136488A
Wear and corrosion resistant nickel-based SiC composite coating for marine hydraulic piston rod and preparation method thereof
CN109628927A